Piloting the use of objective structured clinical examinations (OSCEs) to assess undergraduate medical students’ clinical competence in psychiatry in Zimbabwe - Ruwizhi, Tatenda; Nyamukapa, Ropafadzo; Mazhandu, Fungisai; Mutambara, Julia; Mangezi, Walter; Whitwell, Susannah (Cambridge University Press, 2022)
This report describes a pilot project which involved undergraduate medical students’ clinical competence in psychiatry assessed through objective structured clinical examinations for the first time in Zimbabwe. The pilot describes how gaps in medical education can be addressed by collaborative partnerships that allow sharing of knowledge by local institutions and international experts.